Pengembangan Sistem Manajemen Akuntansi Keuangan Perusahaan untuk Toko Roti Amaya berbasis Website menggunakan React Js - Farah Hanifah Izzati; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Amaya bakery is one of the middle companies based in Malang City who specialized in sell and produce cake and bread. Amaya bakery uses Microsoft Excel to help them make a financial report, but the problem is some of the processes are still manually for example the process of make financial report, transaction validation by an accountant, and invoice send manually via email. Based on the problem, the researcher wants to develop an automatic financial report system. The Development system uses SLDC waterfall methods with react js library and restful API along with MySQL as the database. The system uses MDB React and material-UI as a frontend framework, and lumen as a framework to build API. The system also uses react hooks and stateless components to manage state in react js. Software testing uses on unit and system testing level with the black box and white box strategy.